Identifying Bangla deceptive news using machine learning and deep learning algorithms - Piyal, Anindya Roy; Iqbal, Shams; Rohan, Anupom Ray; Zaman, Nowshin; Meheja, Nowshin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.